2022
DOI: 10.1186/s12910-022-00780-1
|View full text |Cite
|
Sign up to set email alerts
|

Ethical and practical considerations for cell and gene therapy toward an HIV cure: findings from a qualitative in-depth interview study in the United States

Abstract: Background HIV cure research involving cell and gene therapy has intensified in recent years. There is a growing need to identify ethical standards and safeguards to ensure cell and gene therapy (CGT) HIV cure research remains valued and acceptable to as many stakeholders as possible as it advances on a global scale. Methods To elicit preliminary ethical and practical considerations to guide CGT HIV cure research, we implemented a qualitative, in-d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…The perspectives of key populations (e.g., men who have sex with men, people who inject drugs, transgender people, next of kin, community members, and HIV activists) were most often considered when discussing ATI or end-of-life HIV cure research. Key populations accurately understood the meaning and importance of ATIs and end-of-life HIV cure research [ 22 , 53 , 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The perspectives of key populations (e.g., men who have sex with men, people who inject drugs, transgender people, next of kin, community members, and HIV activists) were most often considered when discussing ATI or end-of-life HIV cure research. Key populations accurately understood the meaning and importance of ATIs and end-of-life HIV cure research [ 22 , 53 , 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Across both qualitative and quantitative studies, these studies showed that professionals understand HIV cure clinical research, especially ATIs, as risky, with limited benefits, as some believed no direct health or indirect psychological benefits could be guaranteed [ 43 , 48 , 49 , 83 , 84 ]. The literature also showed that professionals often highlighted physical risks, such as side effects, HIV mutations, and HIV drug resistance, [ 32 , 43 , 48 , 56 , 59 , 66 , 70 , 80 , 81 , 83 86 ] and possible unknown risks [ 32 , 43 , 66 , 70 , 80 , 85 ]. Psychosocial risks, such as unrealistic trial expectations, negative impacts on participants’ social life and mental health, privacy concerns, and HIV transmission to sexual partners were also identified by professionals [ 32 , 43 , 56 , 59 , 66 , 70 , 81 , 84 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations